2018
DOI: 10.1093/humrep/dey025
|View full text |Cite
|
Sign up to set email alerts
|

A diagnostic germ cell score for immature testicular tissue at risk of germ cell loss

Abstract: This study was supported by the Funding Initiative: Translational Research, Ministry of Innovation, Science and Research, Federal State of North Rhine Westphalia (z1403ts006). The authors declare that they do not have competing financial interests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…Similarly, for patients with Klinefelter syndrome, apparent loss of germ cells has been reported prior to puberty, with the appearance of fibrosis in peri-puberty (Van Saen et al 2018). An overall reduction in spermatogonial numbers have also been reported in peripubertal testes from Klinefelter patients compared to controls (Heckmann et al 2018). However, the timing of the loss of spermatogonia cannot be accurately determined from these studies.…”
Section: Pre-existing Testicular Pathologymentioning
confidence: 96%
See 1 more Smart Citation
“…Similarly, for patients with Klinefelter syndrome, apparent loss of germ cells has been reported prior to puberty, with the appearance of fibrosis in peri-puberty (Van Saen et al 2018). An overall reduction in spermatogonial numbers have also been reported in peripubertal testes from Klinefelter patients compared to controls (Heckmann et al 2018). However, the timing of the loss of spermatogonia cannot be accurately determined from these studies.…”
Section: Pre-existing Testicular Pathologymentioning
confidence: 96%
“…A potential limiting factor for development of autologous SSC transplantation is the number of SSCs that can be obtained for transplantation. The SSC population is relatively rare and recent studies using human prepubertal testis tissue have demonstrated the limited quantity of spermatogonia within the testis, which may also be negatively influenced by underlying disease or previous treatments (Poganitsch-Korhonen et al 2017, Heckmann et al 2018) and the small size of biopsy material. Whilst efficient isolation of SSC using specific cellsurface markers is a focus for current research and may significantly increase the yield of human SSC (Zohni et al 2012, Nickkholgh et al 2014a, Valli et al 2014, it is likely that in vitro propagation of the SSC population will also be required in order to generate sufficient SSC to restore fertility in patients.…”
Section: In Vitro Propagation Of Sscsmentioning
confidence: 99%
“…Testicular volumes were determined by palpation using a Prader orchidometer [40] and, in most cases, additionally confirmed by ultrasonography (Table 1). Surgery and testis biopsy collection were performed as previously described [5,41]. The majority of the biopsy was cryopreserved for clinical fertility preservation and the remaining part was fixed in (diluted) Bouin's solution and further processed for histological analysis.…”
Section: Immature Patientsmentioning
confidence: 99%
“…Reasons for this include pathological conditions such as cryptorchidism and genetic or endocrine disorders [1][2][3][4][5]. Apart from that, cancer therapy and conditioning treatments of non-malignant diseases such as sickle cell disease and thalassemia, are known to induce testicular damage, affect spermatogonial function and reduce or even deplete germ cells [4][5][6][7][8][9][10]. Consequently, gonadotoxic treatment may lead to temporary or permanent infertility depending on treatment dose and duration, patients' age and underlying diagnosis [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation